Cost-effectiveness analysis in melanoma detection: A transition model applied to dermoscopy. (November 2016) - Tromme, Isabelle; Legrand, Catherine; Devleesschauwer, Brecht; Leiter, Ulrike; Suciu, Stefan; Eggermont, Alexander; Sacré, Laurine; Baurain, Jean-François; Thomas, Luc; Beutels, Philippe; Speybroeck, Niko
Abstract: Aim: The main aim of this study is to demonstrate how our melanoma disease model (MDM) can be used for cost-effectiveness analyses (CEAs) in the melanoma detection field. In particular, we used the data of two cohorts of Belgian melanoma patients to investigate the cost-effectiveness of dermoscopy. Methods: A MDM, previously constructed to calculate the melanoma burden, was slightly modified to be suitable for CEAs. Two cohorts of patients entered into the model to calculate morbidity, mortality and costs. These cohorts were constituted by melanoma patients diagnosed by dermatologists adequately, or not adequately, trained in dermoscopy. Effectiveness and costs were calculated for each cohort and compared. Effectiveness was expressed in quality-adjusted life years (QALYs), a composite measure depending on melanoma-related morbidity and mortality. Costs included costs of treatment and follow-up as well as costs of detection in non-melanoma patients and costs of excision and pathology of benign lesions excised to rule out melanoma. Results: The result of our analysis concluded that melanoma diagnosis by dermatologists adequately trained in dermoscopy resulted in both a gain of QALYs (less morbidity and/or mortality) and a reduction in costs. Conclusion: This study demonstrates how our MDM can be used in CEAs in the melanoma detection field. The model and the methodology suggested in this paper were applied to two cohorts of Belgian melanoma patients. Their analysis concluded that adequate dermoscopy training is cost-effective. The results should be confirmed by a large-scale randomised study. Highlights: The melanoma disease model previously introduced in this journal was adapted to be used in a cost-effectiveness analysis. Melanoma patient cohorts diagnosed by dermatologists who were, or not, adequately trained in dermoscopy, were compared. The conclusion is that adequate dermoscopy training is cost-effective. Nevertheless, this conclusion should be further supported by a large-scale randomised study.